KARAKTERISASI BATUAN KARBONAT BERDASARKAN GEOMETRI DAN STRUKTUR PORI-PORI - Setyo Wibowo, Andy
Characterization of carbonate rocks is an important part of the development of numerical simulation models. Much effort has been devoted to develop methods for the characterization. Most of the efforts have emphasized either the geological aspect or engineering one. There were some researchers, however, who carried out to link between these two aspects but the details or fundamentals of each aspect for the linkage were somewhat ignored. Indeed, there are the same terms used and understanding gained by both geologist and engineers who deal with reservoir characterization. They connect geological characteristics of rocks with physical properties of the rocks. The connection obtained was based more on the trend observed. This observation resulted in the terms so called rock type. Rock type is defined as rocks or parts of rocks that have been deposited under similar condition and have undergone a similar diagenetic process have similar physical characteristics such as texture or rock fabric, and pore geometry and structure. Each rock type has a certain relationship between physical properties. In many cases, however, no consistency of the existing methods of rock typing has appeared in the petroleum literature. Carbonate rocks in particular are petrophysically recognized as the type of rocks that are commonly more heterogen than siliciclastic rocks. In addition, more than sixty percents of petroleum reserves are contained in carbonate reservoirs. All of these offer ones challenges to conduct further researches on carbonate rocks. The objective of this research therefore was to link the petrophysical properties of carbonate rocks with the details of its geological characteristics. It is well recognized that geological processes has controlled physical properties of the rocks, which are manifestation of both the pores architecture and grain texture or rock fabrics. Pores architecture is commonly described in terms of two pore attributes pore geometry and pore structure. These two terms are thus employed to be related with the microscopic geological features. The very fundamental laws due to Poiseuille and Darcy have been used to describe the pore attributes of porous media. The detailed core descriptions data have also been used to identify and specify the microscopic geological features. The combined Poiseuille and Darcy Laws have been mathematically analysed to produce pore geometry and pore structure that are mainly comprised of permeability and porosity. Furthermore, it has been found that the mathematical relationship of pore geometry ( ) against pore structure ( ) follows power law with an exponent of 0.5 for capillary tube systems, the simplest model for porous media. This relationship indicates a similarity in both pore geometry and pore structure. As many as 1973 core/rock samples obtained from ten carbonate reservoirs that include routine core, SCAL, petrography, SEM and XRD analysis were employed in this research. Comprehensive analysis of all the data was performed to identify and group the rock samples according to similarity of the microscopic geological features. Two data sets originated from two carbonate reservoirs were separated from the others for blind tests. The rest of data sets were used as the main data to investigate the link between geological characteristics and pore geometry and structure. The results of plotting pore geometry against pore structure on log-log graph for all the groups show the formation of straight lines with slopes mostly ranging from 0.206 to less than 0.501. This result strongly demonstrates that a similarity in the microscopic geological features produces a similarity in pore geometry and structure. A systematic decrease observed in the slopes has led to the construction of a type curve for carbonate rock typing. The verification of the type curve has been done by using the two different data sets showing the applicability of the type curve. The results of this research also indicate that the permeability can be predicted as a function of porosity and water saturation and is influenced by rock type. The results of permeability prediction are more accurate than the correlations commonly used in the petroleum industry. Overall, this research has produced consistent characterization of carbonate reservoir rocks dealing with the integration of geological and engineering aspects.